PTH-057 Northern Nutrition Network regional PEG audit: third cycle. (23rd September 2015) - White, S; Torrance, A; Matthewson, K
Abstract : Introduction: The Northern Nutrition Network (NNN) is a multidisciplinary group of individuals with an interest in nutrition representing 17 hospitals in the Northern Region. It meets on a regular basis to promote standards of nutrition. We have previously reported to the Society the results of a 3-month audit by members of the NNN of all PEG insertons in the 17 participating hospitals which was repeated after a 2-year interval.1 The results appeared to show a decline in the rate of PEG insertions and a decline in the 28-day mortality rate following PEG insertion. We performed a further cycle of the audit to see whether the changes had been maintained. Methods: The initial audits were performed from Dec 03 to Feb 04 and Dec 05 to Feb 06. A third cycle was performed from Dec 07 to Feb 08. In order to maintain consistency for each audit the data were recorded using an identical proforma. One individual from each participating unit was responsible for ensuring that data for each PEG insertion was recorded and the Newcastle PEG team collated the data. Results: See Abstract 057 . Conclusion: The decrease in the PEG insertion rate seen between the first and second audit and the decrease in the 28-day mortality rate were only partially maintained. The trend towards less PEG insertion in stroke patients is sustained. There is a trend towards increasing PEG insertion in patients with learning disabilities. PEG insertion rate in demented patients remains low. These prospective audits provide a useful snapshot of PEG insertion practice and trends in 17 different hospitals in the Northern Region.